IMPLEMENTASI ISTIHSAN DALAM PANDANGAN HUKUM EKONOMI SYARIAH - Nadia Ramadani; Dhiauddin Tanjung (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
The aim of this research is to describe the study of Philosophy as a method for understanding Islamic law, especially in the field of sharia economics. The research approach uses qualitative research with the type of documentation or text study research, namely, a series of activities using collecting information relevant to the research topic, reading, taking notes and processing research materials. Meanwhile, analysis is used to carry out deeper discussions based on the information that has been obtained. The results of the research in this paper show that Philosophy is an important option in developing sharia economic law, such as salam sale and purchase contracts, al-istisna', murabahah, online shops, and vending machines which can now be investigated using the Philosophy Science method, apart from that. The advantages of applicable law with the basic aim of Philosophy are to eliminate Mudharat and achieve Ma?la?ah.